Reduced sialidase activity of influenza A(H3N2) neuraminidase associated with positively charged amino acid substitutions. (1st October 2021) - Hussain, Saira; Daniels, Rodney S.; Wharton, Stephen A.; Howell, Steven; Halai, Chandrika; Kunzelmann, Simone; Whittaker, Lynne; McCauley, John W.
Abstract : Neuraminidase (NA) inhibitors (NAI), oseltamivir and zanamivir, are the main antiviral medications for influenza and monitoring of susceptibility to these antivirals is routinely done by determining 50 % inhibitory concentrations (IC50 ) with MUNANA substrate. During 2010–2019, levels of A(H3N2) viruses presenting reduced NAI inhibition (RI) were low ( 0.75 %) but varied year-on-year. The highest proportions of viruses showing RI were observed during the 2013–2014, 2016–2017 and 2017–2018 Northern Hemisphere seasons. The majority of RI viruses were found to contain positively charged NA amino acid substitutions of N329K, K/S329R, S331R or S334R, being notably higher during the 2016–2017 season. Sialidase activity kinetics were determined for viruses of RI phenotype and contemporary wild-type (WT) viruses showing close genetic relatedness and displaying normal inhibition (NI). RI phenotypes resulted from reduced sialidase activity compared to relevant WT viruses. Those containing S329R or N329K or S331R showed markedly higher Km for the substrate and Ki values for NAIs, while those with S334R showed smaller effects. Substitutions at N329 and S331 disrupt a glycosylation sequon (NDS), confirmed to be utilised by mass spectrometry. However, gain of positive charge at all three positions was the major factor influencing the kinetic effects, not loss of glycosylation. Because of the altered enzyme characteristics NAs carrying these substitutions cannot be assessed reliably for susceptibility to NAIs using standard MUNANA-based assays due to reductions in the affinity of the enzyme for its substrate and the concentration of the substrate usually used.